Optimization of drying parameters in the microencapsulation of volatile oil from Spiranthera odoratissima leaves - Souza, Sônia Júlia Oliveira de (2021)
Spiranthera odoratissima A. St.-Hil. (Rutaceae), "manacá", is popularly used for head, muscle aches, rheumatism and, stomach, uterine, renal and liver disorders. The aims of this study were to investigate the physico-chemical and morphological properties of microencapsulated powder of volatile oil from S. odoratissima leaves, optimize the drying process and verify the influence of drying parameters on microencapsulation by spray-drying. The volatile oils from leaves were extracting by hydrodistillation in a Clevenger type apparatus and analyzed by GC/MS. The emulsions were prepared and spray-dried. Box-Behnken experimental model was used for optimize the effects of drying parameters on the encapsulation responses. The β-caryophyllene content in the microcapsules was determined by HPLC. The results suggest that the best operational conditions for the atomization drying of S. odoratissima volatile oil were inlet temperature of 158°C, feed flow of 0.25L/h and drying nozzle diameter of 0.7mm. These results reveal the technological potential of the microcapsules obtained from S. odoratissima volatile oils.